Pelatihan Pembuatan Liquid Smoke Dari Limbah Kelapa Untuk Mendukung Kemandirian Ekonomi Masyarakat Desa Cilentung Kabupaten Pandeglang - Mukhoyyaroh, Qiswatun; Sutisna, Ade Jaya; Junaedi, Yusup; Nugraha, Nugraha; Patricia, Vinda Maharani; Alamsyah, Indra Fajar; Respati, Titik (PPPM POLTESA, 2024)
ABSTRACT Pandeglang is recorded as the district with the highest poverty rate in Banten Province until 2023. This is in contrast to the potential of the resources owned by the region. The superior plantation commodity in the form of coconut is one of the best and most abundant commodities in Banten Province. The problem found in Cilentung Village, Pulosari District, Pandeglang Regency is that people sell coconuts in bulk to the city, then the coconut waste is returned to the village, causing environmental pollution and no innovation in diversification of coconut waste derivative products. The purpose of PkM is to train the community in making Liquid Smoke from coconut waste to support the economic independence of the people of Cilentung Village, Pandeglang Regency. The methods used to answer this problem are socialization of liquid smoke waste into Liquid Smoke, application of pyrolysis technology and coconut waste shredding machines, training in Making Liquid Smoke from Coconut Waste, mentoring and evaluation of activities.